PLEASE ANSWER!!! Select the correct answer from each drop-down menu. Consider the function f(x) = 3x + 1 and the graph of the function g(x) shown below.

PLEASE ANSWER Select the correct answer from each dropdown menu Consider the function fx 3x 1 and the graph of the function gx shown below class=

Respuesta :

Function transformation involves changing the position of a function.

The graph of g(x) is the graph of f(x) translated 2 units right, and [tex]\mathbf{g(x) = 3(x -2) + 1}[/tex]

The function is given as:

[tex]\mathbf{f(x)=3x + 1}[/tex]

The graph of g(x) passes through (2,1) and (0,-5).

Start by calculating the slope (m)

[tex]\mathbf{m = \frac{y_2 - y_1}{x_2 - x_1}}[/tex]

So, we have:

[tex]\mathbf{m = \frac{-5-1}{0-2}}[/tex]

[tex]\mathbf{m = \frac{-6}{-2}}[/tex]

[tex]\mathbf{m = 3}[/tex]

The equation is then calculated as:

[tex]\mathbf{g(x) = m(x -x_1) + y_1}[/tex]

So, we have:

[tex]\mathbf{g(x) = 3(x -2) + 1}[/tex]

By comparing [tex]\mathbf{f(x)=3x + 1}[/tex] and [tex]\mathbf{g(x) = 3(x -2) + 1}[/tex]

The graph of f(x) is shifted 2 units to the right

Read more about function transformation at:

https://brainly.com/question/13810353